Correction of flow stress and determination of constitutive constants for hot working of API X100 pipeline steel. (August 2015) - Qian, Ling-Yun; Fang, Gang; Zeng, Pan; Wang, Li-Xiao
Abstract: Uniaxial compression tests of X100 pipeline steel were conducted to investigate its hot working behavior. Cylindrical specimens were compressed over a wide strain rate range of 0.001–50 s −1 and a temperature range of 850–1100 °C. Due to the heat generated from deformation and friction, the measured temperatures of compressed specimens at higher strain rates (≥1 s −1 ) deviated from the preset temperatures. Therefore, their measured stresses were corrected to obtain the true stresses at the pre-set temperatures before they were used for calculating constitutive equations. The Arrhenius-type constitutive equation was selected to describe the hot working behavior on the basis of corrected stresses. Strain-dependent constitutive constants were determined. The constitutive equation and corrected stress-strain data were both verified by using the results of additional tests at a strain rate of 20 s −1 . Highlights: The flow stresses of pipeline steel X100 at high temperatures were measured. The measured flow stresses were corrected considering the generated deformation heat. The strain-depended constitutive constants were determined to study strain effect. The developed equations were verified by new measured peak stresses.